PENINJAUAN PELAKSANAAN PEKERJAAN PILE CAP PADA PROYEK PEMBANGUNAN FLY OVER GELUMBANG RUAS BTS. KAB OGAN ILIR / BTS. KAB MUARA ENIM – BTS. KOTA PRABUMULIH (PROVINSI SUMATERA SELATAN) - Oktarian, Alvin; Rosyad, Farlin (Ensiklopedia of Journal, 2024)
A pile cap is a structural element used in construction to distribute the load from one or several piles to a wider foundation. The pile cap functions as a load spreader to reduce the pressure received by the foundation and prevent deformation or structural failure. Pile caps are usually made of reinforced concrete and placed at the top of connected piles. Pile cap shapes can vary, including square, rectangular, or circular, depending on the configuration and applied structural loads. Pile caps are also often used to connect and strengthen piles as a whole, thus forming a strong and stable structure. Pile caps are an important component in the construction of buildings, bridges, piers and other structures that use pile foundations.Keywords: Pile cap Foundation, Fly Over construction